Optimizing agricultural value chain in Nigeria through infrastructural development - Martins Iyoboyi; Latifah Musa-Pedro (Agricultural Economics Research Review, 2023)
The paper investigates the impact of infrastructural development on agricultural value chain in Nigeria and finds that infrastructural development has a significant positive impact on the agricultural value chain in the long as well as short run. The macroeconomic instability, on the other hand, exerts the opposite impact. A comprehensive policy framework is required to enhance agricultural value chain output and promote investment in human and physical capital while carefully managing macroeconomic instability and distortions. Governments at all levels should prioritize infrastructural development to optimize the benefits from the agricultural value chain.